STRATEGIC AUTONOMY OF RUSSIA IN THE CHANGING INTERNATIONAL ENVIRONMENT AND CONSEQUENCES FOR THE REGIONAL SECURITY OF THE BALKANS - Proroković, Dušan (Serbian political thought, 2024)
The one-child policy first appeared in the framework of legal regulations in the Republic of China in 1979. According to traditional Chinese beliefs, families with a male heir were considered more respectable and prosperous than families with a female heir. As a large number of families wanted to ensure a male heir, and at the same time to avoid punishment for exceeding the permitted number of children, parents decided on various methods, which today we would call inhumane and criminal. From selective abortions, to hiding the birth of female children, who suffered abuse, starvation and often brutally killed. We will dwell in particular on the phenomenon of selective abortions, which is not only characteristic of China, but also of the greater part of Asia, and has also reached the Balkans. The paper before the readers does not represent a mirror of the positions of ProLife or ProChoice, when it comes to abortions. This paper presents an objective, multidisciplinary view of the phenomenon of selective abortions, which appeared first in the People’s Republic of China, as a result of the introduction of the “one-child policy.” Later it came to India, the Arab world, and for the last two decades it has also been practiced in certain countries of the Balkans (Albania, North Macedonia and Montenegro). The reasons for the so-called “son preference” are different: value system, upbringing, socio-economic reasons. However, the consequences of doing so are unfathomable, since the natural demographic balance between the number of male and female members is disturbed.